Parents' Perceptions of Preschoolers' on the Use of Gadget : Measured by Digital Literacy and Socioeconomic Status - Muliani, Andi St.; Pranoto, Yuli Kurniawati Sugiyo; Formen, Ali (JURNAL PENDIDIKAN USIA DINI, 2024)
The use of gadgets is increasingly prevalent among preschool children, especially in today's digital era. The use of gadgets by preschool children often raises pros and cons among parents and educators, regarding its positive and negative impacts on child development. This type of research is "ex post facto" because it will capture events that have occurred and that contribute to and do not provide treatment to research subjects. The purpose of this study is to examine how much influence digital literacy and socioeconomic status together and individually have on parents' perceptions of gadget use by preschool children in Borongloe Village. Researchers use a non-experimental quantitative approach because it emphasizes objective phenomena and is studied quantitatively. The population in this study were parents who have preschool children in Borongloe Village. Sampling in this study was a saturated sample method where all populations were sampled in the survey which amounted to 55 parents. The results of the study were analyzed using descriptive statistical methods, assumption tests, regression tests, t-tests, and F tests. The results of this study explain that digital literacy and socioeconomic status have a positive and significant effect on parents' perceptions of gadget use in preschool children with a significance value of 0.005;0.001 and 0.000<0.05, respectively.